1983
DOI: 10.1002/lsm.1900030108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laser Sources (Argon, Nd:YAG, CO2) on the Elastic Resistance of the Vessel Wall: Histological and Physical Study

Abstract: The function of elastic elements of the vessel wall is to produce a tension suitable to resist the distension strength made by blood pressure. By producing a modification in the morphologic and structural configuration of such elastic elements, it is possible to obtain changes of the elastic resistance of the wall. The paper reports the histological and physical modifications of blood vessel walls irradiated with different laser sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Fasano, et al, 6 have found that all three lasers have almost identical effects on vessel elastance. which corroborates that of Dew, 5 using argon, C02, and Nd:YAG microsurgical lasers to perform microvascular anastomoses, reveals no significant qualitative difference in the tissue welds produced by these lasers.…”
Section: Lasers In Neurological Surgerymentioning
confidence: 95%
“…Fasano, et al, 6 have found that all three lasers have almost identical effects on vessel elastance. which corroborates that of Dew, 5 using argon, C02, and Nd:YAG microsurgical lasers to perform microvascular anastomoses, reveals no significant qualitative difference in the tissue welds produced by these lasers.…”
Section: Lasers In Neurological Surgerymentioning
confidence: 95%
“…filled with fibrin plugs. The tunica media and adventitia show extensive coagulation necrosis, the extent and depth of the necrotic zone being influenced by the type of laser used [7], For example, using a low-output CO2 laser, Oishi [8] was able to obtain a sufficient laserwelded anastomosis by coagulating only the tunica me dia and adventitia without damaging the intima. The vessel size does not seem to be a limiting factor: vascular structures of 4-5 mm in diameter can be laser-bonded without an apparent increase in complications [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that protein denaturation causes changes in stiffness of the HIFU lesion compared to the surrounding soft tissue (Fasano et al 1983, Consigny et al 1989, Sapin-de Brosses et al 2010). Therefore, axial strain elastography was proposed as a possible technique to visualize HIFU lesion (Stafford et al 1998).…”
Section: Introductionmentioning
confidence: 99%